Analysis of Cognitive Conflict with Intervention on the Understanding of Geometry Concepts in SMA - Iwan Setiawan HR; Alfiah Nurfadhilah AM. Hindi (Universitas Negeri Makassar, 2020)
This research aims to obtain information about students' cognitive conflict analysis with interventions on understanding the concept of geometry. The research method used is descriptive qualitative. This study involved students who experienced cognitive conflict with a sample of 6 students of class XII consisting of 5 female students and 1 male student. To show the data, the instruments used were interview and written questions. Each student has finished delivering answers, which will provide new information that can fill the conflict. Based on the results of the study, it shows that: (1) Cognitive conflict in the nature of a flat shape occurs in understanding the concept of a square with a rectangle and the concept of a rhombus with a square (2) Cognitive conflict for how to find the area of a flat shape occurs in the concept of finding a line area with a rectangle and the concept. The area of a triangle that has a height line inside with an area of a triangle that has a height line outside (3) Cognitive conflict occurs in the concept of calculating the area of a given shape (4) Cognitive conflict occurs in understanding the concept of the relationship between area and perimeter of a shape flat, students understand that a shape that has the same shape but different shapes will also have different circumference.